2014
DOI: 10.1371/journal.pone.0107030
|View full text |Cite
|
Sign up to set email alerts
|

Diapause Induction and Termination in the Small Brown Planthopper, Laodelphax striatellus (Hemiptera: Delphacidae)

Abstract: The small brown planthopper, Laodelphax striatellus (Fallén) enters the photoperiodic induction of diapause as 3rd or 4th instar nymphs. The photoperiodic response curves in this planthopper showed a typical long-day response type with a critical daylength of approximately 11 h at 25°C, 12 h at 22 and 20°C and 12.5 h at 18°C, and diapause induction was almost abrogated at 28°C. The third stage was the most sensitive stage to photoperiod. The photoperiodic response curve at 20°C showed a gradual decline in diap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 28 publications
2
22
3
Order By: Relevance
“…Temperature has been shown to influence diapause in many insect species (e.g., Menaker & Gross, 1965;Kobayashi & Numata, 1995;Wang et al, 2014). However, in contrast to our prediction, temperature does not appear to affect the incidence of diapause in P. glaucus.…”
Section: Figcontrasting
confidence: 99%
“…Temperature has been shown to influence diapause in many insect species (e.g., Menaker & Gross, 1965;Kobayashi & Numata, 1995;Wang et al, 2014). However, in contrast to our prediction, temperature does not appear to affect the incidence of diapause in P. glaucus.…”
Section: Figcontrasting
confidence: 99%
“…In the cabbage beetle Colaphellus bowringi Baly (Coleoptera: Chrysomelidae) and the corn stalk borer Sesamia nonagrioides Lefèbvre (Lepidoptera: Noctuidae), high temperatures (≥25 °C) reduce or avert the diapause‐inducing effect of the photoperiodic signal. The adjustment of the photoperiodic response by temperature has also been reported in many hemipterans . In contrast, in the current study, temperature was not found to have a significant effect on the egg diapause‐induction response of P. gallicus females, at least in the range assayed (18–23 °C).…”
Section: Discussioncontrasting
confidence: 76%
“…The adjustment of the photoperiodic response by temperature has also been reported in many hemipterans. [65][66][67][68] In contrast, in the current study, temperature was not found to have a significant effect on the egg diapause-induction response of P. gallicus females, at least in the range assayed (18-23 ∘ C). The same response was found in other Hemipteran species from similar latitudes, such as the mirid bugs Apolygus lucorum Meyer-Dür and Adelphocoris suturalis Jakovlev (Hemiptera: Miridae) 69 and the bean bug Riptortus clavatus Thunberg (Hemiptera: Alydidae).…”
Section: Discussioncontrasting
confidence: 68%
“…SBPH overwinters with the diapause state in winter (the average temperature 3-5 ∘ C), which is induced by low temperature and short photoperiod. 39 The extreme high temperature can also induce SBPH diapause in The levels of LstrOrco transcripts in insects after feeding rice (CK), dsGFP and dsOrco (with 150 ng μL −1 dsRNA concentration for 4 days), respectively. After qRT-PCR, the levels of LstrOrco transcripts were normalized relative to -actin transcript according to ΔC T algorithm, and the resulting 2 -ΔCt values were used to plot with different feeding treatments as the abscissa.…”
Section: Discussionmentioning
confidence: 99%